ASSESSMENT OF PEDAGOGICAL DIGITAL COMPETENCE - ŠVRČINOVÁ, Veronika (Trends in education, 2020)
Pedagogical Digital Competence (PDC) is a prerequisite for effective applications of digital technology in teaching and learning. In many countries around the world, PDCs are integrated into the educational framework for the teacher. There are also a number of specific PDC frameworks (egUNESCO, ISTE, DigCompTeach, DigCompEdu, ECDL), but there is an acute lack of standardized (self) evaluation tools in the area of PDC assessment. The aim of the paper is to analyze the issue of PDC of teachers in the context, which reflects PDC in the framework of national curricula and reforms of school education systems. The partial objective is to compare the specific frameworks for PDC and to analyze the available (self) PDC assessment tools.
Keywords: Assessment tool; pedagogical digital competence; competence Framework; selfassessment tool.